Links between air quality and economic growth : implications for Pittsburgh - Nataraj, Shanthi (RAND, 2013)
This report assesses the evidence that exists for the ways in which local air quality could influence local economic growth through health and workforce issues, quality-of-life issues, or air-quality regulations and business operations. It then extrapolates some of the existing results to the Pittsburgh region.